Peranan Keluarga dalam Pendidikan Emosional Anak - Yuni Setia Ningsih (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Family is a tiny scope that will bring someone to social life. The fine social order influenced by condition of every family inside it, because society is an accumulation and reflection of lifestyle, world view, even way of thinking of every individual in a family. Good or worse community at social life is depending on family condition. Family is playing important role to direct children to become good moral generation on and beneficial for society. Therefore, to realize that goal, children emotional education from early age at family scope is requirement.Â